Method for manufacturing copper sintered compact
Patent Information
- Application Number
- JP2023137628
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0014】 本開示によれば、電気抵抗率が低い銅焼結体を製造する方法を提供することができる。
Smart Images

Figure 2025031411000001 
Figure 2025031411000002 
Figure 2025031411000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a sintered copper body. [Background technology]
[0002] Electronic components exert their functions by connecting wiring to elements made of semiconductors, magnetic materials, dielectric materials, etc. A well-known method for forming wiring is to print a conductive metal paste on a substrate using a screen printing method and then sinter it. Examples of the metal paste used in the screen printing method include silver paste and copper paste.
[0003] Among these, silver paste is currently used in a wide range of applications because it has excellent oxidation resistance and does not oxidize even when fired in air. However, silver is expensive and has the problem of being prone to migration defects in fine-pitch wiring, so copper paste is being considered as an alternative to silver paste.
[0004] As a method for forming a conductor by firing a copper paste placed on a substrate surface, for example, Patent Document 1 discloses a method in which copper particles in the copper paste are oxidized and fired at a temperature of 350°C or higher and 500°C or lower in a nitrogen gas atmosphere containing an oxidizing gas of 500 ppm or higher and 2000 ppm or lower by volume to obtain a copper oxide sintered body (hereinafter sometimes referred to as an "oxidized sintered body"), and then the oxidized sintered body is reduced to a copper sintered body at a temperature of 400°C or higher and 550°C or lower in a nitrogen gas atmosphere containing 1% or more by volume of a reducing gas. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-004671 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the oxidation firing described in Patent Document 1, the reason for setting the concentration of the oxidizing gas to 2000 ppm or less is explained as follows: If the concentration of the oxidizing gas exceeds 2000 ppm, an extremely dense copper oxide film is formed only on the surface of the copper paste. For this reason, oxygen does not reach the inside of the copper paste, and the paste components before firing remain. As a result, resin and solvent remain inside the sintered body after reduction, which inhibits the formation of a copper sintered body and increases the electrical resistivity.
[0007] Therefore, in Patent Document 1, an atmosphere in which the oxygen concentration is controlled to a certain low range is used to suppress the formation of a dense layer due to rapid oxidation of the paste surface, and oxygen is distributed throughout the paste to form a sintered body.
[0008] However, if the formation of a dense oxidized sintered body is realized throughout the paste, rather than being limited to the paste surface, the copper sintered body after reduction firing is expected to have a lower resistivity than those obtained under previous oxidation / reduction firing conditions.
[0009] An object of the present disclosure is to produce a copper oxidized sintered body having a dense structure and a lower electrical resistivity. [Means for solving the problem]
[0010] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, they have found that a copper sintered body obtained by a manufacturing method including a step of heating a copper paste containing copper particles having an average particle size D50 of 100 nm to 1.2 μm and a binder resin at 350° C. to 600° C. in an oxidizing atmosphere containing an oxidizing gas of more than 2000 ppm by volume to obtain a copper oxide sintered body, and then heating the copper oxide sintered body in a reducing atmosphere, has a low electrical resistivity, and have completed the present disclosure. That is, the present disclosure provides the following.
[0011] (1) A method for producing a copper sintered body, comprising: a first heating step of heating a copper paste containing copper particles having an average particle size D50 of 100 nm or more and 1.2 μm or less and a binder resin at 350° C. or more and 600° C. or less in an oxidizing atmosphere containing an oxidizing gas of more than 2000 ppm by volume to obtain a copper oxide sintered body; and a second heating step of heating the copper oxide sintered body in a reducing atmosphere.
[0012] (2) The method for producing a copper sintered body according to (1), wherein the heating temperature in the second heating step is 130° C. or higher and 600° C. or lower.
[0013] (3) The method for producing a copper sintered body according to (1) or (2), wherein the maximum thickness of the copper paste before heating in the first heating step is 50 μm or less. Effect of the Invention
[0014] According to the present disclosure, a method for producing a copper sintered body having low electrical resistivity can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, the method for producing a copper sintered body according to the present disclosure will be described with reference to specific embodiments, but the method for producing a copper sintered body according to the present disclosure is not limited to the following embodiments.
[0016] <Manufacturing method of copper sintered body> A method for producing a copper sintered body according to an embodiment of the present disclosure includes a first heating step of heating a copper paste containing copper particles having an average particle size D50 of 100 nm or more and 1.2 μm or less and a binder resin at 350° C. or more and 600° C. or less in an oxidizing atmosphere containing an oxidizing gas of more than 2000 ppm by volume, and a second heating step of heating the copper oxide sintered body in a reducing atmosphere.
[0017] It has been found that the copper sintered body obtained by such a method for producing a copper sintered body is fully sintered throughout the entire body, unlike the findings of Patent Document 1 described above, and has a very dense structure. The reason for this is not clear at present, and is not limited to a specific theory, but the present inventors believe it to be as follows. When copper particles having an average particle diameter D50 of 100 nm or more and 1.2 μm or less are used, cracks are generated on the surface of the copper paste during the oxidation firing of the copper paste in the first heating step. Then, since these cracks become a path for introducing oxidizing gas into the copper paste during firing, the oxidation sintering of the copper particles and the decomposition of the binder resin occur sufficiently inside the paste, and finally the cracked parts are sintered and the oxidized sintered body as a whole has a dense structure. After that, in the second heating step, the copper sintered body obtained by reducing the oxidized sintered body also maintains a dense structure similar to that of the oxidized sintered body.
[0018] The copper sintered body thus obtained has a dense sintered structure throughout the entire body and has a low electrical resistivity, making it suitable for use as wiring or electrodes.
[0019] 〔material〕 The substrate and copper paste that can be used for producing a copper sintered body will be described below.
[0020] [substrate] Although not essential, the copper paste described below can be applied to a substrate. Specifically, the substrate is used as a base material for forming a copper sintered film by applying the copper paste to the surface of the substrate. Specifically, the substrate may be a substrate for mounting electronic components, a printed wiring board, or a substrate having through holes.
[0021] The material constituting the substrate is not particularly limited, but examples of the material that can be used include silicon substrates, oxide substrates such as silicate glass, alumina, and quartz, nitride substrates such as silicon nitride and aluminum nitride, carbide substrates such as silicon carbide and titanium carbide, and resin substrates.
[0022] The shape of the substrate is not particularly limited, and a substrate of an appropriate shape can be used depending on the application, etc.
[0023] [Copper paste] The copper paste contains copper particles having an average particle diameter D50 of 100 nm or more and 1.2 μm or less and a binder resin.
[0024] (Copper particles) The copper particles are not particularly limited as long as the average particle diameter D50 is 100 nm or more and 1.2 μm or less. The average particle diameter D50 is preferably 150 nm or more and 200 nm or more. On the other hand, the average particle diameter D50 is preferably 1.15 μm or less, 1.1 μm or less, 1 μm or less, 950 nm or less, 850 nm or less, 750 nm or less, or 700 nm or less. In the present disclosure, the "average particle diameter D50" refers to the particle diameter when the cumulative volume from the small diameter side in the volume-based particle size distribution obtained by a laser scattering diffraction method particle size distribution measuring device is 50%.
[0025] The content of the copper particles is not particularly limited, but is preferably 72 mass% or more, and 74 mass% or more, relative to the total amount of the paste, while the content of the copper particles is preferably 95 mass% or less, 90 mass% or less, 87 mass% or less, and 85 mass% or less.
[0026] (binder resin) The binder resin chemically interacts with the copper particles contained in the paste to impart viscoelasticity to the paste. The binder resin is not particularly limited as long as it is a resin that is decomposed by some treatment such as heating during paste firing. As the binder resin, for example, cellulose resins such as methyl cellulose, ethyl cellulose, and carboxymethyl cellulose, butyral resins, alkyd resins, etc. can be used. Among these, it is preferable to use a cellulose-based resin that tends to react with a trace amount of oxygen or a trace amount of carbon monoxide contained in the firing atmosphere and easily disappear from the paste, and it is more preferable to use ethyl cellulose among the cellulose-based resins.
[0027] The content of the binder resin is not particularly limited, but is preferably 0.05% by mass or more, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more relative to the content of the copper particles, while the content of the binder resin is preferably 3% by mass or less, 2.5% by mass or less, or 2% by mass or less.
[0028] (solvent) The solvent contained in the copper paste is not particularly limited as long as it has an appropriate boiling point, vapor pressure, and viscosity. Specifically, the solvent may be a hydrocarbon solvent, a cyclic ether solvent, an amide solvent, a ketone solvent, an alcohol compound, an ester solvent of a polyhydric alcohol, an ether solvent of a polyhydric alcohol, a terpene solvent, or a mixture thereof. Among these, it is preferable to use texanol, butyl carbitol, butyl carbitol acetate, and terpineol, which have a boiling point of about 200° C., as the solvent. Depending on the relationship between the volatility of the solvent in the copper paste and the drying conditions, etc., the copper paste may be completely solvent-free or the amount of the solvent may be reduced compared to the composition immediately before being applied to the substrate when it is attached to the substrate.
[0029] (Glass Frit) In one embodiment, the copper paste may include a glass frit to better adhere the copper sintered body to the substrate.
[0030] When the copper paste contains glass frit, the content of the glass frit is not particularly limited, but is preferably 0.5 mass% or more, 0.7 mass% or more, 1 mass% or more, 1.5 mass% or more, 2 mass% or more, or 2.5 mass% or more relative to the mass of the copper particles. By having the content of the glass frit be equal to or more than the required value, the adhesion between the copper sintered body and the substrate can be increased. On the other hand, the content of the glass frit is preferably 6 mass% or less, 5 mass% or less, 4.2 mass% or less, 3.2 mass% or less, or 3 mass% or less. By having the content of the glass frit be equal to the required value, the increase in resistance due to the inclusion of the glass frit can be suppressed.
[0031] (Method of manufacturing copper paste) A copper paste can be produced by mixing a binder resin and a solvent, adding copper particles, and kneading the mixture using a device such as a planetary mixer. If necessary, a three-roll mill can be used to improve the dispersibility of the particles.
[0032] (Copper paste application method) In one embodiment, the copper paste may be printed on a substrate using a method such as screen printing to form a desired wiring or electrode shape. In this case, the sintered body is obtained as one disposed on the substrate.
[0033] The paste applied onto the substrate as described above is then dried using a drying oven, a hot plate, or the like.
[0034] The drying temperature is not particularly limited, but is preferably, for example, 80° C. or higher, 90° C. or higher, while the drying temperature is preferably 150° C. or lower, 140° C. or lower, or 130° C. or lower.
[0035] The drying time is not particularly limited, but is preferably, for example, 2 minutes or more, 3 minutes or more, or 4 minutes or more, while the drying temperature is preferably 15 minutes or less, 14 minutes or less, 13 minutes or less, or 12 minutes or less.
[0036] The drying atmosphere is not particularly limited, and may be, for example, under air.
[0037] The maximum thickness of the copper paste before heating in the first heating step is not particularly limited, but is preferably, for example, 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less. By having the maximum thickness be equal to or less than the required value, it is possible to promote oxidation sintering of copper particles and thermal decomposition of resin to the inside of the copper paste. On the other hand, the maximum thickness of the copper paste before heating in the first heating step is preferably 5 μm or more, 7 μm or more. By having the maximum thickness be equal to or more than the required value, it is possible to prevent peeling between the copper sintered body obtained from such copper paste and the substrate after firing. In addition, in this disclosure, the "maximum thickness" refers to the maximum thickness in the entire copper sintered body when the entire copper sintered body on the substrate is three-dimensionally scanned using a laser microscope. In addition, in this disclosure, the "copper paste before heating in the first heating step" refers to the paste immediately before being subjected to heating in the first heating step. For example, if copper paste is applied to a substrate and then dried, "the copper paste before heating in the first heating step" refers to the copper paste after drying. Similarly, if any treatment is performed on the copper paste between application of the paste and the first heating step, it refers to the copper paste after that treatment.
[0038] [First heating step] The first heating step is a step of heating a copper paste containing at least copper particles and a binder resin at 350° C. or more and 600° C. or less in an oxidizing atmosphere containing an oxidizing gas at a volume ratio of more than 2000 ppm.
[0039] The oxidizing gas is not particularly limited as long as it has an oxidizing effect on metallic copper. Specifically, the oxidizing gas may be, for example, one or more selected from the group consisting of oxygen, ozone, sulfur dioxide, and nitrogen dioxide.
[0040] The concentration of the oxidizing gas is not particularly limited as long as it is more than 2000 ppm, but is preferably, for example, 3000 ppm or more, 10000 ppm or more, 50000 ppm or more, or 100000 ppm or more. By having the concentration of the oxidizing gas be greater than the required amount, the sintering of the copper particles and the decomposition of the binder resin are promoted, thereby realizing the expansion of the sintered region and the densification of the sintered body structure, and the electrical resistivity can be reduced. On the other hand, the concentration of the oxidizing gas may be 1000000 ppm (100%) or less, 500000 ppm or less, or 250000 ppm or less.
[0041] In one embodiment, air contains about 21% (about 210,000 ppm) of oxygen as an oxidizing gas, and therefore air can be used as a source of the oxidizing gas.
[0042] The heating temperature in the first heating step is not particularly limited as long as it is 350°C or more and 600°C or less, but is preferably 370°C or more. By setting the heating temperature at a required value or more, the sintered area can be expanded and the sintered body structure can be densified, thereby reducing the electrical resistivity of the copper sintered body. On the other hand, the heating temperature in the first heating step is preferably 550°C or less, 500°C or less, 450°C or less, or 400°C or less. By setting the heating temperature at a required value or less, damage to the substrate (for example, when using resin, etc.) and electronic components mounted on the substrate can be suppressed. In addition, when a silicon substrate is used as the substrate, by setting the heating temperature at a required value or less, an increase in resistance due to a compound generated by the reaction between copper and silicon can be suppressed.
[0043] [Second heating step] The second heating step is a step of heating the copper sintered body obtained in the above-mentioned first heating step in a reducing atmosphere.
[0044] Here, the reducing atmosphere refers to an atmosphere containing a reducing gas. The reducing gas is not particularly limited as long as it has a reducing effect on at least copper oxide, and examples of the reducing gas include hydrogen, carbon monoxide, formic acid, and ammonia.
[0045] The reducing gas concentration is not particularly limited, and is preferably 0.5% or more, 1.5% or more, or 3% or more in terms of volume ratio in the atmospheric gas. By setting the reducing gas concentration at a required value or more, the reduction of copper oxide is promoted, and a copper sintered body having a lower electrical resistivity can be formed. On the other hand, the reducing gas concentration may be 100% or less, 80% or less, 50% or less, or 30% or less.
[0046] The heating temperature in the second heating step is not particularly limited, but is preferably, for example, 180°C or more, 190°C or more, 200°C or more, 210°C or more, 220°C or more, 230°C or more, 240°C or more, 250°C or more, 260°C or more, 270°C or more, 280°C or more, 290°C or more, 300°C or more, 310°C or more, 320°C or more, 330°C or more, 340°C or more, 350°C or more, 360°C or more, or 370°C or more. By setting the heating temperature to a required value or more, the reduction of copper oxide can be promoted, and a copper sintered body with a lower electrical resistivity can be formed. On the other hand, the heating temperature in the second heating step is preferably 600°C or less, 570°C or less, 550°C or less, 520°C or less, 500°C or less, 470°C or less, 450°C or less, 420°C or less, or 400°C or less. By keeping the heating temperature at or below a required value, damage to the substrate (for example, when a resin or the like is used) and electronic components mounted on the substrate can be suppressed. In addition, when a silicon substrate is used as the substrate, by keeping the heating temperature at or below a required value, an increase in resistance due to a compound generated by the reaction between copper and silicon can be suppressed. EXAMPLES
[0047] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.
[0048] [Sample preparation] A copper sintered body sample was produced by the method described below.
[0049] (Preparation of copper paste samples) The mixture was prepared by kneading 80% by mass of copper particles, 6% by mass of ethyl cellulose, and 14% by mass of texanol.
[0050] (Preparation of sintered copper samples) A p-type silicon wafer was treated with phosphoryl chloride (POCl 3 ), phosphorus is diffused onto the surface of the light-receiving side of the silicon wafer to form a high-concentration region of phosphorus, which is called n + This resulted in a silicon wafer having a pn junction.
[0051] The silicon wafer was immersed in a KOH solution to form pyramidal textures with a (111) surface orientation on both sides, and one side of the silicon wafer was polished to remove the texture and make it flat.
[0052] A silicon nitride film with a thickness of 50 nm was formed on the textured surface of the silicon substrate by plasma CVD, and this film was used as an anti-reflection film.
[0053] Using a metal mask with 10 parallel linear openings, each 3 cm long and 60 μm wide, spaced 2 mm apart from the center of the line, 10 lines of copper paste were printed on the surface of the anti-reflective film by screen printing. The maximum thickness was 20 μm. After printing, the substrate was placed on a hot plate and dried in air at 110°C for 10 minutes.
[0054] After drying, the substrate was placed in a firing furnace and heat-treated for 5 minutes in an oxidizing gas atmosphere (oxidation sintering). Next, heat-treated for 5 minutes at 500°C (reduction) in a nitrogen gas atmosphere containing 5% hydrogen gas by volume was performed. After that, the inside of the firing furnace was cooled to room temperature to obtain a copper sintered body sample described later.
[0055] [Sample Evaluation] The copper sintered body samples were evaluated by the following methods.
[0056] (Electrical resistivity) The electrical resistivity of the copper wiring of the test specimen was determined using the DC four-probe method. Four needle-shaped electrodes (probes) spaced 1 mm apart along the length of the copper wiring surface were pressed into contact with each other, a current (I) was passed between the two outer probes, and the potential difference (V) between the two inner probes was measured, and the electrical resistivity (ρ) was calculated from ρ = (V / I) × L / S. Here, S is the cross-sectional area of the wiring, which was determined by observing the cross-section of the wiring with a scanning electron microscope. Additionally, L is the distance between the voltage terminals (1 mm).
[0057] (Adhesion) In the tape test, adhesive tape (3M (registered trademark) Scotch tape, manufactured by 3M Japan Ltd.) was applied to the top of the wiring and rubbed strongly with a finger to adhere, and when the tape was peeled off, it was evaluated whether the copper wiring peeled off from the board. All 10 screen-printed copper sintered bodies were evaluated, and if none of the 10 copper sintered bodies peeled off, it was evaluated as "no peeling", and if peeling occurred in even one copper sintered body, it was evaluated as "yes".
[0058] [Evaluation results] [Test 1: Effect of average particle size D50 of copper particles] Air (oxygen concentration: about 210,000 ppm) was used as the oxidizing gas, the heating temperature in the oxidizing gas atmosphere was set to 400°C, and the copper particles used in the copper paste had an average particle size D50 shown in Table 1. Table 1 shows the evaluation results of the electrical resistivity and the presence or absence of peeling of these samples.
[0059] [Table 1]
[0060] [Test 2: Effect of oxidizing gas content in the first heating step] The average particle diameter D50 was 400 nm, and the heating temperature in the oxidizing gas atmosphere was set to 400°C. In Examples 2-1 to 2-3 and Comparative Example 2-1, nitrogen containing oxygen at the concentration shown in Table 2 was used as the oxidizing gas. On the other hand, in Example 2-4, air (about 210000 ppm) was used. Table 2 shows the evaluation results of the electrical resistivity and the presence or absence of peeling of these samples.
[0061] [Table 2]
[0062] [Test 3: Effect of heating temperature in the first heating step] Copper particles with an average particle diameter D50 of 400 nm were used, air (oxygen concentration: approximately 210,000 ppm) was used as the oxidizing gas, and the heating temperature in the oxidizing gas atmosphere (heating temperature in the first heating step) was set to the temperature shown in Table 3. Table 3 shows the evaluation results of the electrical resistivity and the presence or absence of peeling of these samples.
[0063] [Table 3]
[0064] From the above, it was found that a copper sintered body produced by a production method including heating a copper paste containing copper particles with an average particle size D50 of 100 nm or more and 1.2 μm or less and a binder resin at 350°C or more and 600°C or less in an oxidizing atmosphere containing more than 2000 ppm by volume of oxidizing gas to obtain a copper oxide sintered body, and then heating the copper oxide sintered body in a reducing atmosphere, does not peel off from the substrate and has a low electrical resistivity of less than 4.0 μΩcm.
Claims
1. A first heating step of heating a copper paste containing copper particles having an average particle diameter D50 of 100 nm to 1.2 μm and a binder resin at 350 ° C. to 600 ° C. in an oxidizing atmosphere containing an oxidizing gas of more than 2000 ppm by volume to obtain a copper oxide sintered body; A second heating step of heating the copper oxide sintered body in a reducing atmosphere. A method for manufacturing sintered copper bodies.
2. The heating temperature in the second heating step is 180° C. or more and 600° C. or less. The method for producing the copper sintered body according to claim 1.
3. The maximum thickness of the copper paste before heating in the first heating step is 50 μm or less. The method for producing the copper sintered body according to claim 1 or 2.
Citation Information
Patent Citations
Sintering method of copper paste
JP2016004671A
Cited By
Method for producing sintered copper object
WO2026164297A1